Public Health Surveillance for Mental Health - Elsie J. Freeman, MD, MPH; Lisa J. Colpe, PhD, MPH; Tara W. Strine, MPH; Satvinder Dhingra; Lisa C. McGuire, PhD; Laurie D. Elam-Evans, PhD, MPH; Geraldine S. Perry, DrPH, RD (Centers for Disease Control and Prevention, 2010)
Public health systems have relied on public health surveillance to plan health programs, and extensive surveillance systems exist for health behaviors and chronic disease. Mental health has used a separate data collection system that emphasizes measurement of disease prevalence and health care use. In recent years, efforts to integrate these systems have included adding chronic disease measures to the Collaborative Psychiatric Epidemiology Surveys and depression measures to the Behavioral Risk Factor Surveillance System; other data collection systems have been similarly enhanced. Ongoing challenges to integration include variations in interview protocols, use of different measures of behavior and disease, different interval reference periods, inclusion of substance abuse disorders, dichotomous vs continuous variables, and approaches to data collection. Future directions can address linking surveillance efforts more closely to the needs of state programs, increasing child health measurements in surveys, and improving knowledge dissemination from survey analyses.